Analysis of student adjustment in dormitory based on type of school, cultural background and grade level - Rusnila, Rusnila; Daharnis, Daharnis; Syukur, Yarmis (Universitas Negeri Padang, 2021)
Adjustment is a process that includes mental and behavioral responses to achieve balance in meeting needs in accordance with environmental demands. However, it was found that students had difficulty adjusting, such as being unprepared to live in a dormitory, having difficulty being away from their parents, violating the dormitory rules, having difficulty getting along, and having intercultural disputes. This is thought to be related to differences in schools, cultural backgrounds and grade levels. This research aims to analyze the adjustment of students in the dormitory based on the type of school, cultural background, and grade level. This research method used is ex post facto with a factorial analysis design. The population was 200 students in the dormitory of Al-Faruqi Kampar, Riau. This research uses a self-adjustment instrument with Alpha Cronbach of 0.876. The data were analyzed using the technique Analysis of Variance (ANOVA). The results showed that the level of adjustment of students based on the type of school was in the high category and there were significant differences in the adjustment of students based on the type of school, the level of adjustment of students based on the cultural background was high category and there was no significant difference in the adjustment of students based on cultural background. The level of adjustment based on grade level high category and there is no significant difference in adjustment based on grade level, and there is no interaction between these variables in explaining the adjustment of students in the dormitory. The implications of the results of this research can be used as a reference for counselors in schools for the preparation of guidance and counseling service programs to improve student adjustment in dormitories.